Sankofa: Looking Back at my Practice Encounter with Witchcraft, HIV/AIDS and Disability in Ghana - Vyda Mamley Hervie (Journal of Comparative Social Work, 2015)
Social work students are trained to develop and maintain a professional sense of integrity, particularly when working in environments beyond their control. Using critical reflection as an example, students are encouraged to pause and reflect during practice encounters, which entails a reassessment of the situation. The aim is to help transform taken for granted ways of thinking and doing things into best practices. In this sense, students are provided with perspectives on theoretical frameworks and encouraged to appreciate the essence of maximizing practice through a culture of learning and reflection. Through the approach of critical reflection, students are also encouraged to understand how power functions in society, especially through ways in which an individual attempts to maintain unequal social relations. Critical reflection therefore helps students to fill knowledge gaps on how to discover and address inequalities in practice situations.